Synthesis of Indole/Benzofuran-Containing Diarylmethanes through Palladium-Catalyzed Reaction of Indolylmethyl or Benzofuranylmethyl Acetates with Boronic Acids - Arcadi, Antonio; Calcaterra, Andrea; Chiarini, Marco; Fabrizi, Giancarlo; Fochetti, Andrea; Goggiamani, Antonella; Iazzetti, Antonia; Marrone, Federico; Marsicano, Vincenzo; Serraiocco, Andrea (Synthesis, 2021)
The palladium-catalyzed synthesis of indole/benzofuran-containing diarylmethanes starting from indolylmethyl or benzofuranylmethyl acetates with boronic acids has been investigated. The success of the reaction is influenced by the choice of precatalyst: with indolylmethyl acetates the reaction works well with [Pd(η3-C3H5)Cl]2/XPhos while with benzofuranylmethyl acetates Pd2(dba)3/XPhos is more efficient. The good to high yields and the simplicity of the experimental procedure make this protocol a versatile synthetic tool for the preparation of 2- and 3-substituted indoles and 2-benzo[b]furans. The methodology can be advantageously extended to the preparation of a key precursor of Zafirlukast.
Keywords: palladium; boronic acids; Suzuki–Miyaura reaction; indoles; benzofurans; diarylmethanes